Reproductive performance and weaning success in fur-chewing chinchillas (Chinchilla lanigera) - Galeano, Maria G. (2014)
In captive chinchillas, one of the most challenging behavioral problems is the development of a stress-related abnormal repetitive behavior (ARB) known as ‘‘fur-chewing’’. We investigated whether there is a relationship between the severity of fur-chewing behavior and reproductive function in male and female chinchillas. Regardless of the severity of abnormal behavior, fur-chewing males did not show significant differences in seminal quality (sperm concentration, motility and viability; integrity of sperm membrane and acrosome) and the response to the process of semen collection (the number of stimuli needed to achieve ejaculation) when compared to those with normal behavior. Also, females showing normal or fur-chewing behavior presented similar reproductive performance in terms of number of litters per female per year and litter size. However, pup survival rate was lower ( p = 0.05) in fur-chewing females than in normal females. These results seem to be consistent with data suggesting non-significant effects of ARBs on reproductive performance.